Inhibition Effect of Extract of Psychotria viridiflora Stem on α-Amylase and α-Glucosidase and Its Application in Lowering the Digestibility of Noodles - Chen, Qimin; Toy, Joanne Yi Hui; Seta, Cynthia; Yeo, Tiong Chia; Huang, Dejian (Frontiers in Nutrition, 2021)
A collection of tropical medicinal plants from East Malaysia’s rainforest are used by indigenous tribes for their curative properties. Despite their healing properties, these forest plant species are still largely unexplored hence remain virtually unknown to the outside world. In this study, the anti-diabetic properties of Psychotria viridiflora plant that is used for the treatment of diabetes by a local community in Sarawak, Malaysia were investigated. Ethyl acetate (EA) extract of P. viridiflora stem was found to exhibit high starch hydrolase inhibition activity with an IC50 value of 15.4 2.1g/mL against porcine α-amylase and an IC50 value of 32.4 3.7 g/mL against rat intestinal α-glucosidase. A complex mixture of A-type oligomeric proanthocyanidins containing (epi)fisetinidol, (epi)afzelechin, (epi)guibourtinidol and (epi)catechin were found to be responsible for the starch hydrolase inhibition activity. Ethyl acetate (EA) extract of P. viridiflora stem was then incorporated into wheat and rice flour to reformulate noodles with slow digestibility and was assessed under In vitro simulated gastrointestinal conditions. A dose-dependent effect on digestibility was observed for both noodles upon incorporating 1-6% (w/w) of EA extract, with noodles containing 6% (w/w) extract exhibiting the greatest reduction in digestibility. As compared to rice noodles containing 6% extract (31.16% inhibition), wheat noodles with the same extract concentration had a smaller decline in digestibility (27.25% inhibition) after 180 min. Overall, our findings highlighted the potential of P. viridiflora in the prevention of postprandial hyperglycaemia.